2009
DOI: 10.1093/jxb/erp167
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial signal peptide is functional in plants and directs proteins to the secretory pathway

Abstract: The Escherichia coli heat-labile enterotoxin B subunit (LT-B) has been used as a model antigen for the production of plant-derived high-valued proteins in maize. LT-B with its native signal peptide (BSP) has been shown to accumulate in starch granules of transgenic maize kernels. To elucidate the targeting properties of the bacterial LT-B protein and BSP in plant systems, the subcellular localization of visual marker green fluorescent protein (GFP) fused to LT-B and various combinations of signal peptides was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 80 publications
0
27
1
Order By: Relevance
“…The trafficking pathway of recombinant proteins in plants is a subject that has recently arisen great interest because it directly affects the developing of effective strategies in molecular farming (Moeller et al 2009). This is also true for foreign proteins expressed in transformed plastids, where further investigations on their correct folding can stimulate the exploration of fundamental questions about plastid protein quality control mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The trafficking pathway of recombinant proteins in plants is a subject that has recently arisen great interest because it directly affects the developing of effective strategies in molecular farming (Moeller et al 2009). This is also true for foreign proteins expressed in transformed plastids, where further investigations on their correct folding can stimulate the exploration of fundamental questions about plastid protein quality control mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, we did not add specific sub-cellular targeting sequences in our construct, but rather conserved the native bacterial signal peptide, which results in targeting to the secretory pathway of maize. 42 This is the first report of a recombinant protein under the control and direction of the endosperm specific promoter and bacterial signal peptide, respectively, being enriched in the fiber fraction. We anticipate that recombinant proteins controlled and directed using similar regulatory elements and targeting sequences will have similar fates in the wet-milling fractionation process.…”
Section: Discussionmentioning
confidence: 91%
“…10,21 It is commonly thought that the fine fiber fraction contains mostly cell wall remnants from endosperm cells. Our previous studies 42 have shown that LT-B accumulates in the secretory system of endosperm cells when carrying its native signal peptide. It is our hypothesis that the association of LT-B to the fine fiber fraction obtained from wet-milling fractionation is the result of tissue specific expression and sub-cellular compartmentalization in the secretory system of endosperm cells.…”
Section: Resultsmentioning
confidence: 96%
“…Another example is the linker AG, a simple alanine-glycine linker of six amino acids with three AG repeats (AGAGAG). When added between LT-B and GFP (green fluorescent protein),using oligonucleotide extensions in the PCR (polymerase chain reaction) primers as part of the expression cassette in the vectors pLM03, pLM08, pLM09 with the percentage of TSP of LT-B::GFP being line dependent, and the accumulation went from undetectable to 0.059 extracted in maize kernels (Moeller, Gan, & Wang, 2009). Modified linkers can improve the level of protein accumulation in the case of the FV single chain linked to the CH3 of a human anti-rat transfer in receptor IgG3 heavy chain by the flexible and optimized linker (GGGGS)3, and transformed stably into mammalian cells (Trinh, Gurbaxani, Morrison, & Seyfzadeh, 2004).…”
Section: Linkers In Plant Molecular Pharmingmentioning
confidence: 99%